Sequential Reasoning in Electricity: Developing and Using a Three-Tier Multiple Choice Test - Urban, Hildegard (Scientia in educatione, 2017)
Electricity is one of the areas in physics most studied in terms of learning difficulties. Misconceptions are strongly-held, stable cognitive structures, which differ from expert conception and affect how students understand scientific explanations. Therefore, there is a need for tests of conceptual understanding tests which are useful in diagnosing the nature of students’ misconceptions related to simple electric circuits and, in consequence, can serve as a valid and reliable measure of students’ qualitative understanding of simple electric circuits. As ordinary multiple choice tests with one-tier may overestimate the students’ correct as well as wrong answers, two- and three-tier tests were developed by researchers. Although, there is much research related to students’ conceptions in basic electricity, there is a lack of instruments for testing basic electricity concepts of students at grade 7, especially addressing an electric circuit as a system for a simple circuit of resistors and lamps in series. To address this gap, the context of the present study is an extension to the development of an already existing instrument developed by the author for testing electricity concepts of students at grade 7, specifically focusing on only two specific aspects in depth: first, to develop three-tier items for figuring out sequential reasoning, and second, to distinguish between misconceptions and lack of knowledge. The participants of the study included 339 secondary school students from grade 7 to 12 after instruction on electricity. Surprisingly, there are no dependences on students’ misconceptions either according to their gender or to their age. In conclusion, the findings of the study suggest that four items for uncovering students’ sequential reasoning can serve as a valid and reliable measure of students’ qualitative understanding of the systemic character of an electric circuit.